1999
DOI: 10.1016/s0885-3924(98)00150-x
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Chronic Cancer Pain in a Cancer Hospital in the Netherlands

Abstract: In a prospective study of 313 Dutch cancer patients with chronic pain, the practice of pain treatment was evaluated by means of Donabedian's structure-process-outcome framework. The practice of pain treatment was assessed by: (1) structural resources, describing the setting in which pain treatment is provided; (2) process components, which describe the clinical practice; and (3) outcome measures, which refer to patients' pain intensity, patient satisfaction, or composite pain management index scores. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 55 publications
(88 reference statements)
1
14
1
Order By: Relevance
“…A large proportion of patients with cancer pain, e.g., 80% (Beauregard, Pomp, & Choiniere, 1998) to 99% (Panteli & Patistea, 2007), and postoperative pain, e.g., 75% have reported a high degree of satisfaction with pain management despite reporting moderate to severe pain intensity. Similar study results have been found in other countries, including the Netherlands, Sweden and China (Beauregard et al, 1998; de Wit, van Dam, Vielvoye-Kerkmeer, Mattern, & Abu-Saad, 1999; Hurwitz, Morgenstern, & Yu, 2005; Jensen, Mendoza, Hanna, Chen, & Cleeland, 2004). Possible explanations for this dissonance are varied.…”
Section: Literature Reviewsupporting
confidence: 91%
“…A large proportion of patients with cancer pain, e.g., 80% (Beauregard, Pomp, & Choiniere, 1998) to 99% (Panteli & Patistea, 2007), and postoperative pain, e.g., 75% have reported a high degree of satisfaction with pain management despite reporting moderate to severe pain intensity. Similar study results have been found in other countries, including the Netherlands, Sweden and China (Beauregard et al, 1998; de Wit, van Dam, Vielvoye-Kerkmeer, Mattern, & Abu-Saad, 1999; Hurwitz, Morgenstern, & Yu, 2005; Jensen, Mendoza, Hanna, Chen, & Cleeland, 2004). Possible explanations for this dissonance are varied.…”
Section: Literature Reviewsupporting
confidence: 91%
“…Various studies have discredited the correlation between pain intensity and patient satisfaction. 7,20,33 Although this might be the case for a minority of patients, this large cohort indicates that there is indeed correlation. There is no doubt that there are highly satisfied patients regardless of their pain levels, because previous studies have shown that most patients report high satisfaction regardless of pain levels.…”
Section: Tts-f For Intolerable Cancer Painmentioning
confidence: 86%
“…1,3,7,9,14,17,21,27,29,34 Overall, the side effects gradually declined from an increase after initial application, thus warranting close surveillance for the first few days of application to fairly steady levels by 2 months. Interestingly, the rate and duration of side effects in the opioid naïve population to patients with opioid tolerance was fairly short and matched that of a more closely monitored group of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The patient is the best expert on his or her own disease, and it is crucially important that the family is closely involved in the team together with doctors, nurses, and other health professionals. The management of cancer pain is still not satisfactory in Finland or even in other European countries [5,23]. The rate of morphine use remains much lower in Finland than in the other Scandinavian countries, in spite of sometimes heated public debate and a growing body of research evidence [21,22,24].…”
Section: Introductionmentioning
confidence: 99%